Macroeconomic News and Stock Returns in the United States and Germany - Funke, Norbert (IMF Working Papers; Working Paper ;, 2002)
Using daily data for the January 1997 to June 2002 period, we analyze the impact of a broad set of macroeconomic news on stock prices in the United States and Germany. With GARCH specifications we test five hypotheses and find that news on real economic activity has a significant impact on stock prices. The effects vary between different types of stocks and depend on the state of the economy. In a boom period, bad economic news may be good news for stock prices. For German stock prices, international news is at least as important as domestic news. The analysis of bihourly data suggests that the main effect occurs within a short period of time.